Ответы и объяснения

2013-04-12T18:34:57+04:00

cos^4a-sin^4a=cos2a

cos^4a-sin^4a=cos^2a-Sin^2a

Cos^4a-sin^4a-cos^2a+sin^2a=0

cos^4a-(1-cos^4a)-cos^2a+(1-cos^2a)=0

cos^4a-1+cos^4a-cos^2a+1-cos^2a=0

2cos^4a-acos^2a=0

2cos^2a(2cos^2a-1)=0

cos^2a=0                   2cos^2a-1=0

cosa=0                        cos^2a=1\2

a=π\2+πn                    cosa=1\2            cosa=-1\2

                                      a=±π\3+2πn       a=±(π-arccos(-1\2))+2πn

                                                                    a=±2π\3+2πn